The interplay of oxidative stress and inflammation in pediatric patients with nephrotic syndrome - Simachew, Yonas Mulat; Mihajlović, Marija; Antonić, Tamara; Miloševski-Lomić, Gordana; Peco-Antić, Amira; Jovanović , Dragana; Paripović, Dušan; Stefanović, Aleksandra (Journal of Medical Biochemistry, 2023)
Summary Background: The pathophysiological mechanisms crucial in the development of nephrotic syndrome (NS) in the pediatric population are still not fully understood. This study aims to investigate the synergistic interaction of oxidative stress and inflammation in the pathogenesis of NS. Additionally, one of the objectives of this study is to examine the relationship between hypertension and the degree of oxidative stress and inflammation in patients during the acute phase of the disease. Methods: The study included 33 children, aged 2 to 9 years, with NS. Blood samples were collected during the acute phase and remission. Parameters of oxidative status were determined, including total oxidative status (TOS), advanced oxidation protein products (AOPP), prooxidant-antioxidant balance (PAB), sulfhydryl groups (-SH), paraoxonase 1 (PON1), and total antioxidant status (TAS) in serum, measured spectrophotometrically. Inflammatory parameters such as pentraxin 3 (PTX3), leptin, programmed cell death ligand 1 (PD-L1), and E-cadherin were determined using enzyme-linked immunosorbent assay (ELISA).Results: Patients with NS and hypertension had significantly higher levels of AOPP and TOS (p=0.029 and p=0.003, respectively). During the acute phase of the disease, lower activity of -SH and PON1 was observed compared to remission (p
Keywords: Nephrotic syndrome; Oxidative stress; Inflammation; Hypertension; Pentraxin 3; Advanced oxidation protein products